Procedures for measuring and verifying gastric tube placement in newborns: an integrative review - Flávia de Souza Barbosa Dias; Suellen Cristina Dias Emidio; Maria Helena Baena de Moraes Lopes; Antonieta Keiko Kakuda Shimo; Ana Raquel Medeiros Beck; Elenice Valentim Carmona
ABSTRACT Objective: to investigate evidence in the literature on procedures for measuring gastric tube insertion in newborns and verifying its placement, using alternative procedures to radiological examination. Method: an integrative review of the literature carried out in the Cochrane, LILACS, CINAHL, EMBASE, MEDLINE and Scopus databases using the descriptors "Intubation, gastrointestinal" and "newborns" in original articles. Results: seventeen publications were included and categorized as "measuring method" or "technique for verifying placement". Regarding measuring methods, the measurements of two morphological distances and the application of two formulas, one based on weight and another based on height, were found. Regarding the techniques for assessing placement, the following were found: electromagnetic tracing, diaphragm electrical activity, CO2 detection, indigo carmine solution, epigastrium auscultation, gastric secretion aspiration, color inspection, and evaluation of pH, enzymes and bilirubin. Conclusion: the measuring method using nose to earlobe to a point midway between the xiphoid process and the umbilicus measurement presents the best evidence. Equations based on weight and height need to be experimentally tested. The return of secretion into the tube aspiration, color assessment and secretion pH are reliable indicators to identify gastric tube placement, and are the currently indicated techniques.